2016
DOI: 10.1242/jcs.180356
|View full text |Cite
|
Sign up to set email alerts
|

Reverse overshot water-wheel retroendocytosis of Apo Transferrin extrudes cellular iron

Abstract: Iron a vital micronutrient for all organisms must be managed judiciously as both, deficiency or excess can trigger severe pathology. While cellular iron import is well understood its export is thought to be limited to transmembrane extrusion via ferroportin the only known mammalian iron exporter. Utilizing primary cells and cell lines (including those with no discernible expression of ferroportin on their surface) we demonstrate that upon iron loading the multifunctional enzyme Glyceraldehyde-3-phosphate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…FPN (SLC40A1), a member of the large solute carrier gene family (slc) is a transmembrane protein primarily expressed in macrophages, duodenal, and hepatic cells and is considered the only (or major) iron exporter, a role confirmed by the finding that mice with global FPN inactivation died during embryonic development . However, a recent study suggested an alternative pathway of cellular iron export mediated by GAPDH‐dependent retroendocytosis of iron‐loaded Tf . In addition, considering that NO has a high affinity for iron and can form dinitrosyl‐dithiol iron complexes (DNIC) and that iron can also be bound to GSH, the multidrug resistance protein ATP‐binding cassette subfamily C 1 (ABCC1), which exports both DNIC and GSH out of cells, may represent a way of iron efflux, particularly in activated murine macrophages that synthesize large amounts of NO .…”
Section: Iron Exportmentioning
confidence: 99%
“…FPN (SLC40A1), a member of the large solute carrier gene family (slc) is a transmembrane protein primarily expressed in macrophages, duodenal, and hepatic cells and is considered the only (or major) iron exporter, a role confirmed by the finding that mice with global FPN inactivation died during embryonic development . However, a recent study suggested an alternative pathway of cellular iron export mediated by GAPDH‐dependent retroendocytosis of iron‐loaded Tf . In addition, considering that NO has a high affinity for iron and can form dinitrosyl‐dithiol iron complexes (DNIC) and that iron can also be bound to GSH, the multidrug resistance protein ATP‐binding cassette subfamily C 1 (ABCC1), which exports both DNIC and GSH out of cells, may represent a way of iron efflux, particularly in activated murine macrophages that synthesize large amounts of NO .…”
Section: Iron Exportmentioning
confidence: 99%
“…In addition to TfR1 and TfR2, the multifunctional molecule GAPDH has been reported to work as a TfR in different cell types (Raje et al, 2007; Kumar et al, 2012) with a role in iron uptake and/or iron export (Sheokand et al, 2016) and as a chaperone for intracellular heme traffic (Sweeny et al, 2018). Relevant to brain and excitotoxicity, GAPDH interacts with the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid subtype of glutamate receptors in the neurons without glutamate stimulation and has also been reported to be pivotal for axon development (Lee et al, 2016).…”
Section: Iron Uptake and Handling By Parenchymal Brain Cellsmentioning
confidence: 99%
“…While according to current dogma, iron leaves the cell principally via Fpn transport, it is worth noting that some data suggest that cellular ferritin efflux may be a mechanism for Fe 3+ export (42)(43)(44)(45). Moreover, a recent study proposed an alternative iron export pathway, via GAPDH-mediated retro-endocytosis of iron-loaded Tf (46), and an important but underappreciated iron-release mechanism employed by tumor-associated Mɸs (TAMs) to kill cancer cells has been described. In this context, M1-like TAMs produce NO via iNOS that evokes iron efflux from cancer cells (47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%